Monstrous beauty - Fama, Elizabeth 1965- (Farrar Straus Giroux, 2012)
In alternating chapters, tells of the mermaid Syrenka's love for Ezra in 1872 that leads to a series of horrific murders, and present-day Hester's encounter with a ghost that reveals her connection to the murders and to Syrenka